An industrial scale process for the enzymatic removal of steryl glucosides from biodiesel - Peirú, Salvador (2015)
Background: Biodiesels produced from transesterification of vegetable oils have a major quality problem due to thepresence of precipitates, which need to be removed to avoid clogging of filters and engine failures. These precipitateshave been reported to be mostly composed of steryl glucosides (SGs), but so far industrial cost-effective methods toremove these compounds are not available. Here we describe a novel method for the efficient removal of SGs frombiodiesel, based on the hydrolytic activity of a thermostable β-glycosidase obtained from Thermococcus litoralis.Results: A steryl glucosidase (SGase) enzyme from T. litoralis was produced and purified from Escherichia coli culturesexpressing a synthetic gene, and used to treat soybean-derived biodiesel. Several optimization steps allowed for theselection of optimal reaction conditions to finally provide a simple and efficient process for the removal of SGs fromcrude biodiesel. The resulting biodiesel displayed filterability properties similar to distilled biodiesel according to thetotal contamination (TC), the cold soak filtration test (CSFT), filter blocking tendency (FBT), and cold soak filter blockingtendency (CSFBT) tests. The process was successfully scaled up to a 20 ton reactor, confirming its adaptability toindustrial settings.Conclusions: The results presented in this work provide a novel path for the removal of steryl glucosides from biodieselusing a cost-effective, environmentally friendly and scalable enzymatic process, contributing to the adoption ofthis renewable fuel.